Policing communal spaces. A reconfiguration of the 'Mass Private Property' hypothesis - Kempa, Michael (The British journal of criminology, 2004)
Explanations for developments in state and non-state policing include the influence of globalization/late-modernity (Reiner 1992; Sheptycki 1995), shifts in political rationalities (O'Malley and Palmer 1996; O'Malley 1997), the rise of mass private property' (Shearing and Stenning 1981; 1983), and the decline of secondary social controls (Jones and Newburn 2002). Responding positively to recent critiques of the mass private property hypothesis raised by Jones and Newburn (1998; 1999a), we argue that shifts in policing can be tied to the resurgence of many new forms of communal space' (von Hirsch and Shearing 2000; Hermer et al. 2002) of which mass private property is only one example. We then induce a framework suggestive of the links between the extant accounts of trends in policing